Relevance of Value and Determinants of Restatement Financial Statements - Fery Wijaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The reported financial statements have a general purpose, namely to provide information about the company's financial position, performance and cash flows that are useful for most users of financial statements in order to make investment decisions and demonstrate management's stewardship for the use of resources entrusted to them. they. The purpose of this study was to determine and analyze the effect of restatement of financial statements on firm value. Profitability, leverage, firm size and audit quality together can explain the possibility of a financial statement restatement.